Hello, my first polynomial root problem!

Algebra Level 4

36 x 8 481 x 6 + 1466 x 4 481 x 2 + 36 = 0 \large 36x^{8} - 481x^{6} + 1466x^{4} - 481x^{2} + 36 = 0

Let a a and b b be the largest and smallest integral roots of the polynomial equation above respectively. Find the value of 673 a + b + 1 673a + b + 1 .


The answer is 2017.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Apr 19, 2017

36 x 8 481 x 6 + 1466 x 4 481 x 2 + 36 = 0 Dividing both sides by x 4 36 x 4 481 x 2 + 1466 481 x 2 + 36 x 4 = 0 36 x 4 + 72 + 36 x 4 481 x 2 481 x 2 + 1394 = 0 36 ( x 2 + 1 x 2 ) 2 481 ( x 2 + 1 x 2 ) + 1394 = 0 A quadratic equation of x 2 + 1 x 2 ( 4 ( x 2 + 1 x 2 ) 17 ) ( 9 ( x 2 + 1 x 2 ) 82 ) = 0 \begin{aligned} 36x^8-481x^6+1466x^4-481x^2+36 & = 0 & \small \color{#3D99F6} \text{Dividing both sides by }x^4 \\ 36x^4-481x^2+1466-\frac {481}{x^2}+\frac {36}{x^4} & = 0 \\ 36 x^4 + 72 + \frac {36}{x^4} - 481 x^2 - \frac {481}{x^2} + 1394 & = 0 \\ 36 {\color{#3D99F6} \left( x^2 + \frac 1{x^2} \right)}^2 - 481 {\color{#3D99F6}\left(x^2 + \frac 1{x^2} \right)} + 1394 & = 0 & \small \color{#3D99F6} \text{A quadratic equation of } x^2 + \frac 1{x^2} \\ \left(4\left(x^2 + \frac 1{x^2} \right)-17\right)\left(9\left(x^2 + \frac 1{x^2} \right)-82 \right) & = 0 \end{aligned}

{ 4 x 2 17 + 4 x 2 = 0 4 x 4 17 x 2 + 4 = 0 9 x 2 82 + 9 x 2 = 0 9 x 4 82 x 2 + 9 = 0 \implies \begin{cases} 4x^2 -17 + \dfrac 4{x^2} = 0 & \implies 4x^4 -17x^2 + 4 = 0 \\ 9 x^2 - 82 + \dfrac 9{x^2} = 0 & \implies 9x^4 -82x^2 + 9 = 0 \end{cases}

4 x 4 17 x 2 + 4 = 0 ( 4 x 2 1 ) ( x 2 4 ) = 0 x = ± 1 2 , ± 2 \begin{aligned} 4x^4 -17x^2 + 4 & = 0 \\ (4x^2 - 1)(x^2-4) & = 0 \\ \implies x & = \pm \frac 12, \ \pm 2 \end{aligned}

9 x 4 82 x 2 + 9 = 0 ( 9 x 2 1 ) ( x 2 9 ) = 0 x = ± 1 3 , ± 3 \begin{aligned} 9x^4 -82x^2 + 9 & = 0 \\ (9x^2 - 1)(x^2-9) & = 0 \\ \implies x & = \pm \frac 13, \ \pm 3 \end{aligned}

Therefore, a = 3 a=3 , b = 3 b=-3 and 673 a + b + 1 = 2017 673a + b + 1 = \boxed{2017}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...